Developing an academic English-task based language teaching training program for secondary school teachers - Francisquete, Mary Jean M. (2008)
This study designed a teachers' training program that would encourage public secondary teachers to think more systematically of Task-Based Language Teaching as a basis for teacher development. Teacher-participants knowledge of task was determined through a needs analysis. The instrument used was the Task-Based Language Teaching Knowledge Questionnaire. Components of the training program were identified by setting criteria and was revised afterward through a comparison of the pretest and the posttest. The study revealed that the smallest knowledge of the teacher-participants for the pre-test was on the category on the Different Aspects of TBLT and more knowledge of TBLT. Posttest results showed an overturn of the pretest results. About 20 to 20.59 percent of the items for each category needs further enhancement as the teacher-participants still have misconceptions of TBLT which could be attributed to the limited time given to conduct the training.